1999
DOI: 10.1021/bi981946c
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Integrin αVβ3−Ligand Interface by Photoaffinity Cross-Linking

Abstract: Integrins are cell surface adhesion molecules involved in mediating cell-extracellular matrix interactions. High-resolution structural data are not available for these heterodimeric receptors. Previous cross-linking studies of integrins aimed at elucidating the nature of the receptor-ligand interface have been limited to identification of relatively large binding domains. To create reagents for "photoaffinity scanning" of the RGD-binding site of human integrin alpha V beta 3, new conformationally constrained l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 40 publications
1
32
2
1
Order By: Relevance
“…The ligand-binding domains of the human ␣ v and ␤ 3 subunits have been determined using a number of methods, most prominently photoaffinity cross-linking and generation of chimeric receptors with closely related ␣ v and ␤ 3 subunits. These studies have estimated that the ligand-binding regions for the ␣ v and ␤ 3 subunits lie between amino acid residues 1 and 340 (41,57) and between residues 85 and 207 (13,19,39,56,61,62), respectively (amino acid residue 1 is the first amino acid after cleavage of the signal sequence). Within this domain, the amino acid sequence similarity between bovine and human sequences was quite high for the ␣ v subunit (98.8%) but was only 93.5% for the ␤ 3 subunit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligand-binding domains of the human ␣ v and ␤ 3 subunits have been determined using a number of methods, most prominently photoaffinity cross-linking and generation of chimeric receptors with closely related ␣ v and ␤ 3 subunits. These studies have estimated that the ligand-binding regions for the ␣ v and ␤ 3 subunits lie between amino acid residues 1 and 340 (41,57) and between residues 85 and 207 (13,19,39,56,61,62), respectively (amino acid residue 1 is the first amino acid after cleavage of the signal sequence). Within this domain, the amino acid sequence similarity between bovine and human sequences was quite high for the ␣ v subunit (98.8%) but was only 93.5% for the ␤ 3 subunit.…”
Section: Resultsmentioning
confidence: 99%
“…Although ␣ v ␤ 3 was originally called the vitronectin receptor, it can bind to other ligands (33). While it is clear that both the ␣ and ␤ subunits of integrins structurally contribute to ligand binding (22,34), there are specific regions of the ␣ v (41, 57) and ␤ 3 (13,19,39,56,61,62) subunits that have been identified as directly interacting with ligands. At least two other picornaviruses can utilize ␣ v ␤ 3 to initiate infection, coxsackievirus A9 (CAV9) (53) and echovirus 9 (48).…”
mentioning
confidence: 99%
“…To further define the reasons for the observed specificities among the ␤ subunits, we exchanged regions of the subunits' putative LBDs. The regions we chose to exchange have been identified functionally as LBDs by various biochemical criteria, and exchanging these regions among ␤ subunits resulted in changes in the ligand specificities of the integrins (11,18,40,69,70). The recently solved crystal structure of the ␣ V ␤ 3 integrin, which has led to the structural definition of the integrin's LBD, showed that the region exchanged in this study interacts with the ␣ subunit within the ligand-binding cleft and contains the RGD binding site, but the entire LBD of the ␤ subunit appears to encompass a larger region of the ectodomain than that exchanged in this study (74,75).…”
Section: Discussionmentioning
confidence: 99%
“…For example, fibronectin precursor contains 5 motifs of NGXG, which are likely serving as binding sites with integrin ␣3. To definitively prove that integrin ␣3 is indeed the receptor for pA, one should perform photoaffinity labeling or chemical cross-linking experiments that involves covalent modification of the target receptor with the peptide followed by mass-spectroscopic analysis [24,25].…”
Section: Discussionmentioning
confidence: 99%